INCREASING STUDENT'S ABILITY IN ACCOMPLISHING THE PROBLEM RESOLUTIONS OF NATURAL RESOURCE MATERIAL RESOURCES BY USING ROUND CARD TECHNICAL QUESTIONS METHOD AT CLASS IV OF MIS AR-RASYID - Diah Hafizhotul Husna (State Islamic University of North Sumatra Indonesia, 2018)
This study aims to determine the ability to solve the natural resources science material in class IV MIS Ar-Rashid through methods of questioning technique round card This type of research is classroom action research conducted in three cycles. In cycle I consists of 2 meetings, cycle II and cycle III consists of 1 meeting. Every cycle there are activities of planning, execution, observation and reflection. Subjects in this study were students of class IV as many as 24 students consisting of 13 male students and 11 female students. While the object of this study is the level of ability to solve the natural resource IPA material by applying the question and answer method of round card techniques. Based on the data analysis after the granting of action obtained in the first cycle there are 4 complete students (19.04%) who obtained the category of finishing ability the material of natural resources is still very low and 11 students are unfinished (80,95%) or reach mastery learning with average class 50,09. In cycle II, there were 10 complete students (47,61%) who got the category of ability to solve the Natural Resource Science material is very low and 14 unfinished students (52,38%) with the average class 71,80. In cycle III, there were 18 complete students (85,71%) who got the ability category to finish the natural resource high science material (reaching completeness study), and 6 unfinished students (14,29%) with the average class 77.90. Thus it can be concluded that the use of question and answer methods round card techniques can improve the ability to solve the natural resource IPA materials so that this method can be used as an alternative learning